The association of beta‐2 adrenoceptor genotype with short‐cervix mediated preterm birth: a case–control study. (20th January 2015) - Miller, R; Smiley, R; Thom, EA; Grobman, WA; Iams, JD; Mercer, BM; Saade, G; Tita, AT; Reddy, UM; Rouse, DJ; Sorokin, Y; Blackwell, SC; et al.
<x xml:space="preserve">Abstract</x> Objective To determine whether β2‐adrenoceptor (β2AR) genotype is associated with shortening of the cervix or with preterm birth (PTB) risk among women with a short cervix in the second trimester. Design A case–control ancillary study to a multicentre randomised controlled trial. Setting Fourteen participating centres of the Maternal‐Fetal Medicine Units Network of the Eunice Kennedy Shriver National Institute of Child Health and Human Development. Population Four hundred thirty‐nine women, including 315 with short cervix and 124 with normal cervical length. Methods Nulliparous women with cervical length <30 mm upon a 16–22‐week transvaginal sonogram and controls frequency‐matched for race/ethnicity with cervical lengths ≥40 mm were studied. β2AR genotype was determined at positions encoding for amino acid residues 16 and 27. Main outcome measures Genotype distributions were compared between case and control groups. Within the short cervix group, pregnancy outcomes were compared by genotype, with a primary outcome of PTB <37 weeks. Results Genotype data were available at position 16 for 433 women and at position 27 for 437. Using a recessive model testing for association between short cervix and genotype, and adjusted for ethnicity, there was no statistical difference between cases and controls for Arg16 homozygosity (OR 0.7, 95% CI 0.4–1.3) or Gln27 homozygosity (OR 0.9, 95% CI 0.3–2.7). Among cases, Arg16 homozygosity was not associated with protection from PTB or spontaneous PTB. Gln27 homozygosity was not associated with PTB risk, although sample size was limited. Conclusions β 2AR genotype does not seem to be associated with short cervical length or with PTB following the second‐trimester identification of a short cervix. Influences on PTB associated with β2AR genotype do not appear to involve a short cervix pathway.